The Arabic Version of Injury-Psychological Readiness to Return to Sport Scale: Translation and Psychometric Validation - Osama R. Abdelraouf; Amr A. Abdel-Aziem; Nouf H. Alkhamees; Zizi M. Ibrahim; Mohamed A. Elhosiny; Shaza E. Ibrahim; Amal A. Elborady (Medicina)
Background and Objectives: It is crucial to consider not only the physical variables but also the athlete’s psychological condition prior to making the decision to return to sport (RTS). It is unfortunate that there is currently no universal questionnaire available in Arabic to determine whether an athlete is ready to return to sports. So, this cross-cultural validation study was carried out to translate and validate the Injury-Psychological Readiness to Return to Sport Scale (I-PRRS) into the Arabic language. Materials and Methods: One hundred twenty athletes with lower extremity injuries (95 males and 25 females) completed the Arabic I-PRRS twice with a one-week time interval. An additional 50 athletes, comprising 40 males and 10 females, also participated in the study by completing the questionnaire during their initial visit to a physical therapist. Floor and ceiling effects, internal consistency, reliability, discriminate validity, convergent validity, and factor construct were analyzed. Results: The I-PRRS was translated into Arabic with no floor or ceiling effects. It had good internal consistency (0.84) and excellent test–retest reliability (ICC 0.88, 95% CI 0.73–0.95) where the lower bound of 95% CI indicated at least good reliability. The SEM was 1.14, and the MDC was 3.27 points. Athletes who were cleared to RTS demonstrated significant differences in their responses compared with those who were visiting their physical therapist for the first time. These differences were significant across all individual items, as well as in the total scores of the assessment (p < 0.001). There was a significant moderate correlation between overall scores on the I-PRRS and the Tampa Scale of Kinesiophobia (TSK) (rs = 0.69, p < 0.05). Conclusions: The Arabic version of the I-PRRS demonstrated good reliability and validity, making it a suitable tool for evaluating psychological readiness to RTS among injured athletes in Arabic-speaking populations.